PENGARUH CORPORATE GOVERNANCE DAN INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Diana Lestari; Raja Adri Satriawan; Supriono - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of Corporate Governance and inventory intensity to tax management. Corporate governance consisting of number board of commissioner, percentage Independent Commissioner, Audit Committee, and compensation of commissioner and executive. This study is manufacture companyfor years 2011-2013 selected by using method of pusposive sampling. There are 147 companies fulfilling criterions. This study used Multiple regression analysis was conducted using SPSS version 17.00 for windows. The result of this study that the variables that affect the tax management is number board of commissioner, independent commissioner, audit committee, and compensation of commissioner and excecuive. While variable that did not affect the tax management is inventory intensity.Keywords: tax management, corporate governance, and inventory intensity